TERAPI LATIHAN DAN AKTIFITAS FUNGSIONAL PADA LANSIA DI DESA RAYA KAHEAN KABUPATEN SIMALUNGUN TAHUN 2020 - Nurul Rahmah Siregar (Jurnal DIKMAS, 2020)
The purpose of training therapy and functional activities in the elderly is to increase understanding of how to do exercise therapy and increase functional activities in the elderly in Raya Kahean Village, Simalungun Regency. The implementation method carried out in this community service activity is by conducting two-way discussions or communication and by conducting demonstrations by strengthening the process of internalizing knowledge because of direct practice carried out to the community, especially the elderly. The activity plan carried out is by conducting surveys, analyzing the needs of the elderly, socializing exercise therapy programs and functional activities to the elderly, as well as carrying out exercise therapy programs and functional activities, as well as evaluating whether the program is able to improve the health of the elderly in Raya Kahean Village, Simalungun Regency